TRADITIONAL CULINARY TRANSFORMATION IN PANDAAN: ANALYZING FLAVOR AND PRESENTATION INNOVATION OF SATE KOMOH - Hadi, Bawa Mulyono; Taufiq, Achmad; Lie, Tjhing Man (Transpublika Publisher, 2025)
Traditional culinary is an important part of cultural heritage that continues to undergo transformation in line with the times and consumer tastes. This study aims to analyse the taste and presentation innovation of Sate Komoh in Pandaan as part of the dynamics of traditional culinary. Using a qualitative method with a case study approach, data was collected through observation, in-depth interviews with culinary businesses, and documentation. The results show that innovation in flavour variants, the use of alternative raw materials, and more modern presentation techniques are the main factors in maintaining Sate Komoh's relevance amidst competition in the culinary industry. In addition, digital marketing strategies also play a role in increasing the attractiveness and accessibility of this product for the younger generation. With these innovations, Sate Komoh not only survives as a culinary speciality of Pandaan but also has the potential to develop more widely in the national culinary market. This research underlines that innovations in taste, processing techniques, presentation, and digital marketing strategies play a strategic role in maintaining the sustainability and increasing the competitiveness of traditional culinary, especially Sate Komoh in Pandaan. The positive response of consumers to this adaptation shows that the transformation carried out is not only able to maintain existence, but also expand market reach to the national level through digitalisation and product diversification such as frozen food.